Do women athletes` experiences of menstrual function and dysfunction vary across competition levels? A mixed methods exploration - Adam, M. E.; Bristow, A.; Neely, K. C.; Erlandson, M. C. (Psychology of Sport and Exercise, 2022)
Menstrual dysfunction is a common phenomenon in sport and many women describe that their menstrual cycle can negatively impact their sport participation, performance, and experiences. However, there is little research examining if competition level plays a role in women athletes` rates and experiences of menstrual function and dysfunction. Therefore, the purpose of this study was to explore and describe rates and experiences of menstrual function and dysfunction among athletes of differing competition levels. An online mixed methods approach was applied. Women athletes (N = 63), between 14 and 39 years of age (M = 24.20, SD = 6.53), competing in a range of sports from the local to international level completed an anonymous interview style survey to generate data. Data analysis for this project was an iterative and integrated process where quantitative and qualitative data were considered together and are represented through reported statistics and generated themes. Although group differences were hypothesized, no differences based on competition level in rates or experiences of menstrual dysfunction were observed. In addition to detailed descriptive statistics, five themes were generated: Normalizing Dysfunction; Menstrual Symptoms; Clothing as a Distraction; Participation Impact; and Regaining Control. In line with previous research, the women in this study experienced a range of menstrual dysfunctions that impacted their sport experiences. However, this study highlights that regardless of competition level or sport type women face challenges in sport regarding menstrual function and due to the normalization of dysfunction in sport women athletes` health and well-being are not always supported.